(untitled) (Polis (Santiago), 2021)
This article seeks to know the experiences of women working in a public state university, a gendered and commercialized workplace, in the context of a pandemic. For this, through a qualitative methodology, four focus groups were developed with the participation of academic, administrative and contingent workers. The analysis carried out confirms the presence of patriarchal structures that reify traditional gender relations, a burden and overload that affects everyone. However, the experiences are dissimilar, depending on the contract and corresponding responsibilities. Finally, the article proposes universities develop gender-sensitive policies to mitigate the consequences of the pandemic on female workers.